Overview of Student Organizational Activities in the Scouting Extracurricular Program atSMA Negeri 8 Padang - Ilham Sidiq, Pajri; Wisroni, Wisroni (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
This research is background by the high discipline of scout members in participating in scout extracurricular activities at SMA N 8 Padang, which is thought to be influenced by the activeness of students in organizations. This study aims to see an overview of the activeness of student organizations in participating in scout extracurricular activities at SMA N 8 Padang. This type of research is descriptive quantitative. The population in this study were all students who took part in scout extracurricular activities at SMA Negeri 8 Padang. The population is 29 people and 70% of the sample taken is 22 people using simple random sampling. The data collection technique uses a questionnaire, with data collection tools in the form of a list of written statements or a questionnaire. The data analysis technique uses the percentage formula. The results showed that: (1) participation in management was very active (2) getting to know and being known by the school environment was active (3) often visiting the secretariat of the organization was active (4) in responding to problems very active (5) in communicating, discussing, and very active in coordinating (6) in expressing opinions very active (7) in spending time very active (8) in having information about the organization very active (9) in contributing very actively. It is suggested to coaches to be able to maintain scout extracurricular activities which are already very good and also be able to add and improve activities related to scout extracurriculars at SMA N 8 Padang.Keywords: liveliness, discipline, scout extracurriculars